2015
DOI: 10.1371/journal.pone.0132510
|View full text |Cite
|
Sign up to set email alerts
|

Erectile Dysfunction in Patients with Sleep Apnea – A Nationwide Population-Based Study

Abstract: Increased incidence of erectile dysfunction (ED) has been reported among patients with sleep apnea (SA). However, this association has not been confirmed in a large-scale study. We therefore performed a population-based cohort study using Taiwan National Health Insurance (NHI) database to investigate the association of SA and ED. From the database of one million representative subjects randomly sampled from individuals enrolled in the NHI system in 2010, we identified adult patients having SA and excluded thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 43 publications
0
28
0
1
Order By: Relevance
“…Being the most common type of sleep-disordered breathing, sleep apnea (SA) is usually characterized by repetitive shallowing and stopping of breaths during sleep, which is usually accompanied with intermittent hypoxia, arousal, and sleep fragmentation [ 8 ]. Polysomnography (PSG) is usually performed to establish the diagnosis of SA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Being the most common type of sleep-disordered breathing, sleep apnea (SA) is usually characterized by repetitive shallowing and stopping of breaths during sleep, which is usually accompanied with intermittent hypoxia, arousal, and sleep fragmentation [ 8 ]. Polysomnography (PSG) is usually performed to establish the diagnosis of SA [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…2e6 Epidemiological and clinical studies have shown that erectile dysfunction (ED) shares similar comorbidities with OSA. 7 A series of studies conducted with sleep medical center patients as participants have reported that the prevalence of ED in patients with OSA ranges from 41% to 80%. 8e11 In a large population-based cohort study, researchers found that people with OSA exhibited an increased risk of ED; this study reported an ED incidence 9.44fold higher in the apnea cohort than that in the nonapnea cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Erectile dysfunction (ED) shares similar comorbidities with OSA [6,7]. The association between sleep disordered breathing and sexual dysfunction was first described by Guilleminault et al [8] in 1981, when they reported a 48% ED rate in men with severe OSA.…”
Section: Introductionmentioning
confidence: 99%